Permeability estimation of tight sandstone from pore structure characterization. (January 2022) - Qiao, Juncheng; Zeng, Jianhui; Chen, Dongxia; Cai, Jianchao; Jiang, Shu; Xiao, Enzhao; Zhang, Yongchao; Feng, Xiao; Feng, Sen
Abstract: Permeability, a crucial parameter in the subsurface geological and industrial activities, is highly heterogeneous in tight sandstone. Great difficulties and accuracy losses present in the permeability estimation of tight sandstone owing to its intricate pore structures. In this paper, to obtain reliable permeability estimation models for tight gas sandstone, the popular Coates, Schlumberger Doll Research, and Pittman models are improved from a systematic pore structure characterization. The characterization, integrating multiple techniques and incorporating percolation theory and fractal model, identifies the presences of three pore structure types, involving the mixed pore type, single-pore dominant type, and dual porous type. Attribute differences are discovered in the pore constitute, size distribution, microscopic heterogeneity, and connectivity of different structure types, in which disparate structural variation rules are identified in the pore-controlled and dual porous structures. These differences are responsible for the distinctions in the continuous fluid percolation pathways. The pore-controlled sandstone shares similar reticular networks with variations in extension degrees, while the dual porous sandstone exhibits a completely different tubular network, indicating different permeability variation mechanisms. Differed correlation trends between pore attributes and permeability in pore-controlled and dual porous tight sandstone suggest that permeability is primarily affected by pore structure type, followed by connectivity. The permeability of pore-controlled tight sandstone is determined by the pore geometrical features and influenced by connectivity and heterogeneity, while that of dual porous one is controlled by the attributes of micro cracks. Modification is performed on the Coates, SDR, and Pittman models by taking pore structures, particularly the structure types and connectivity, into account. Evident performance enhancements occur in these calibrated models. The excellent applicability of the improved models in pore-controlled tight sandstone confirms that pore structural types should be addressed in priority, followed by pore connectivity, in the permeability estimation of tight sandstone. Highlights: Pore structure is probed by integrated techniques, fractal model, and percolation theory. Pore-controlled and dual porous tight sandstone exhibits differed pore attribute variations. Permeability is primarily controlled by pore structure type, followed by connectivity. Permeability estimation is improved by considering structural type and connectivity. Improved models show perfect adaptability in pore-controlled tight sandstone.